MODAL SOSIAL, COPING EKONOMI, GEJALA STRES SUAMI DAN KESEJAHTERAAN SUBJEKTIF KELUARGA PADA KELUARGA TKW - Silitonga, Mirdat; puspitawati, Herien; Muflikhati, Istiqlaliyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2018)
The achievement of family well - being is an aspiration of all families including families of migrant workers, to achieve the well - being of one of the ways that the families of migrant workers with the departure of the wife work as domestic servants in various countries. The purpose of this study was to analyze social capital, economic coping, sress symptomâ€™s husband and family subjektive well - being of women migrant workers. This research use cross sectional studies. The location was chosen purposively in Tanggeung Village, Pagermaneuh Village, Margaluyu Village, Karangtengah Village, Tanggeung District and Pasirdalam Village Kadupandak District, Cianjur, West Java, Indonesia. Seventy five families were selected purposively among the families of women migrant workers. The finding indicates that social capital is in the moderate category, the coping economy is in the moderate category, the sress symptomâ€™s husband is in the low category and the family well-being is in the low category. Finding in this study family subjective well-being is influenced by income per capita, sress symptomâ€™s husband and economic coping. Keywords: economic coping, family subjective well-being, social capital, stress symptom Abstrak Kesejahteraan keluarga merupakan sesuatu yang ingin dicapai seluruh keluarga, termasuk keluarga Tenaga Kerja Wanita (TKW), untuk mencapai kesejahteraan tersebut salah satu cara yang dilakukan oleh keluarga TKW adalah mengirim istri sebagai pembantu rumah tangga di berbagai negara. Tujuan dari penelitian ini adalah untuk menganalisis modal sosial, coping ekonomi, gejala stres suami, dan kesejahteraan subjektif keluarga TKW. Penelitian ini menggunakan cross sectional studies. Lokasi dipilih dengan metode purposive di Provinsi Jawa Barat, Kabupaten Cianjur, Kecamatan Tanggeung, Desa Pagermaneuh, Desa Marguluyu, Desa Karangtengah, Desa Tanggeung, Kecamatan Kadupandak, Desa Pasirdalam. Jumlah sampel sebanyak 75 keluarga TKW dengan metode purposive sampling. Penelitian ini menemukan modal sosial berada pada kategori sedang, coping ekonomi berada pada kategori sedang, gelaja stres suami berada pada kategori rendah, dan kesejahteraan subjektif berada pada kategori rendah. Penelitian ini juga menemukan kesejahteraan keluarga berpengaruh terhadap pendapatan perkapita, gelaja stres suami, dan coping ekonomi. Kata kunci : coping ekonomi, gejala stres, kesejahteraan subjektif, modal sosial. References [BPS] Badan Pusat Statistik. 2016. Data provinsi termiskin 2016. Berita Resmi Statistik [internet]. 4 Januari 2016. [diunduh 2016 September 7]; Tersedia pada: http://www.bps.go.id. [BPS] Badan Pusat Statistik Jawa Barat. 2016. Garis Kemiskinan Menurut Kabupaten/Kota di Jawa Barat (Rp/kapita/bulan), 2005-2014. Berita Resmi Statistik [internet]. 4 Januari 2016, [diunduh 2016 September 7]; Tersedia pada: http://jabar.bps.go.id. Alfiasari. 2008. Analisis modal sosial dalam pemberdayaan ekonomi keluarga miskin di Kelurahan Kedung Jaya, Kecamatan Tanah Sareal, Kota Bogor. Vol. 1 no. 1 edisi Januari. Bogor (ID): Institut Pertanian Bogor. Borner, Shively J, Wunder G, Wyman S. 2012. How do rural households respond to economic shocks? Insights from hierarchical analysis using global data. International Association of Agricultural Economists. Casey L. 2013. Stress and wellbeing in Australia survey 2013. Australian Psychological Society Carbonell A F. 2005. Income and well-being: an empirical analysis of the comparison income effect. Journal of Public Economics: 89 (2005) 997 â€“ 1019. Coleman J S. 1988. â€œSocial capital in the creation of human capital.â€ American Journal of Sociology 94 (Supplement): S95-S120. Celia M, Lenore M. 2004. Somali Women and Well-Being: Social Networks and Social Capital among Immigrant Women in Australia. Human Organization. Vol. 63 :88 Djohan R. 2008. Leader & Social Capital : Lead to Togetherness. Jakarta: Fund Asia Education Debebe Z, Mebratie A, Sparrow R, Abebaw D, Dekker M, Alemu G, Bedi A. 2013. Coping with shocks in rural Ethiopia. Working Paper. African Studies Centre. Dercon S. 2000. Income risk, coping strategies and safety nets. Background paper World Development Report 2000/01: Centre for the Study of African Economies, Oxford University, Department of Economics Diener E, Tay L. 2013. Rising Income and the Subjective Well-Being of Nations. Journal of Personality and Social Psychology: Vol. 104, No. 2, 267â€“276 DOI: 10.1037/a0030487 Dwyer A, Cummings A. 2001. Stress, Self-Efficacy, Social Support, and Coping Strategies in University Students. Canadian Journal of Counselling. Vol. 35:3 Ersado L, Alderman H, Alwang J. 2014. Changes in Consumption and Saving Behavior before and after Economic Shocks: Evidence from Zimbabwe. http://www.jstor.org/stable/10.1086/380136 Fujiwara F, Kawachi I. 2008. Social Capital and Health A Study of Adult Twins in the U.S. American Journal of Preventive Medicine. Vol. 35: 2 Garcia M, McDowell T. 2010. Mapping Social Capital: A Critical Contextual Approach For Working with Low-Status Families. Journal of Marital and Family Therapy. Vol. 36 No. 1: 96. 10.1111/j.1752-0606.2009.00188.x Grootaert C. 1999. Social capital, household walfare and poverty in Indonesia. Working Paper, No.6. Washington DC, USA: The World Bank. Social Development Department. Hasanah U, Nadiroh, Neolaka A. 2017. The Influence of Couple Interaction, Roles Differences, and Social-Economic Status on Motherâ€™s Stress Coping. American Scientific Publisher. Vol. 23 10868 â€“ 10870. Helliwell J F, Huang H, Wang S. 2013. Social Capital and Well-Being in Times of Crisis. Journal Happiness Study: DOI 10.1007/s10902-013-9441-z Headey B, Wooden Mark. 2004. The Effects of Wealth and Income on Subjective Well-Being and Ill-Being. Melbourne Institute of Applied and Social Research: IZA DP No. 1032. Hyyppa M. T, Maki J. (2003). Social participation and health in a community rich in stock of social capital. Health Education Research, 18(6), 770â€“779. Hossain S. 2006. Poverty, household strategies, and coping with urban life: examining livelihood framework in Dhaka City, Bangladesh. Bangladesh e-Journal of Sociology, Vol. 2, No. 1. Jain A K, Giga S I, Cooper C L. 2013. Stress, Health and Well-Being: The Mediating Role of Employee and Organizational Commitment. International Journal of Environmental Research and Public Health: doi:10.3390/ijerph10104907 Jaya, Sumertajaya I M, 2008, Pemodelan persamaan struktural dengan partial least square. Semnas Matematika dan Pendidikan Matematika. Vol. 1 118 - 132 Jha R, Nahrajan H K, Pradhan K. 2012. Household Coping Strategies and Welfare: Does Governance Matter? NCAER Working Papers on Decentralisation and Rural Governance in India. Krantz. 2001. The Sustainable Livelihood Approach to Poverty Reduction. Swedish International Development Cooperation Agency Kawachi I. 2006 Commentary: social capital and health: making the connections one step at a time. Int J Epidemiol. Vol. 35:989 â€“93. Lazarus, R S, Folkman, S, 1984. Stress, Appraisal, and Coping. New York: Springer. Mohnen S, Beate V B, Flap H, Subramanian S, Groenewegen P. 2015. The Influence of Social Capital on Individual Health: Is it the Neighbourhood or the Network?. Soc Indic Res. Vol. 121:195â€“214 DOI 10.1007/s11205-014-0632-8 Markovic, M, Manderson, L. (2002). Crossing national boundaries: Social identity formation among recent immigrant women in Australia from former Yugoslavia. Identity: An International Journal of Theory and Research, 2, 303-316. Puspitawati H. 2012. Gender dan Keluarga. Bogor (ID): IPB Press. ____________. 2013. Ekologi Keluarga: Konsep dan Lingkungan. Bogor (ID): IPB Press. ____________. 2013. Pengantar Studi Keluarga. Bogor (ID): IPB Press. Puspitawati H, Herawati T. 2013. Metode Penelitian Keluarga. Bogor (ID): IPB Press. Rebecca P, Crnic K A, Cox M J, Mills W R. 2013. The Family Model Stress and Maternal Psychological Symptoms: Mediated Pathways From Economic Hardship to Parenting. Journal of Family Psychology: DOI: 10.1037/a0031112 Rosidah U, Hartoyo, Istiqlaliyah. 2012. Kajian strategi koping dan perilaku investasi anak pada keluarga buruh pemetik melati gambir. Jurnal Ilmu Keluarga dan Konsumen, Vol. 5, No. 1. Stevenson B, Wolfers J. 2013. Subjective Well-Being and Income: Is There Any Evidence of Satiation? American Economic Review. 103(3): 598â€“604 http://dx.doi.org/10.1257/aer.103.3.598 Welsh J A, Berry H L. 2009. Social capital and mental health and well-being. National Centre for Epidemiology and Population Health, The Australian National University Wills E, Orozco L, Forero C, Pardo O, Andonova V. 2011. The relationship between perceptions of insecurity, social capital and subjective well-being: Empirical evidences from areas of rural conflict in Colombia. The Journal of Socio-Economics. Vol. 40 88â€“96 Yip W, Subramanian S. V, Mitchell A D, Lee D, Wang J, Kawachi I. 2007. Does social capital enhance health and well-being? Evidence from rural China. Journal Social Science & Medicine: 35 â€“ 49